Balancing Light Absorption and Charge Transport in Vertical SnS2 Nanoflake Photoanodes with Stepped Layers and Large Intrinsic Mobility. Issue 31 (9th July 2019) - Giri, Binod; Masroor, Maryam; Yan, Tao; Kushnir, Kateryna; Carl, Alexander D.; Doiron, Curtis; Zhang, Haochuan; Zhao, Yanyan; McClelland, Arthur; Tompsett, Geoffrey A.; Wang, Dunwei; Grimm, Ronald L.; et al.
Abstract: Significant optical absorption in the blue–green spectral range, high intralayer carrier mobility, and band alignment suitable for water splitting suggest tin disulfide (SnS2 ) as a candidate material for photo‐electrochemical applications. In this work, vertically aligned SnS2 nanoflakes are synthesized directly on transparent conductive substrates using a scalable close space sublimation (CSS) method. Detailed characterization by time‐resolved terahertz and time‐resolved photoluminescence spectroscopies reveals a high intrinsic carrier mobility of 330 cm 2 V −1 s −1 and photoexcited carrier lifetimes of 1.3 ns in these nanoflakes, resulting in a long vertical diffusion length of ≈1 µm. The highest photo‐electrochemical performance is achieved by growing SnS2 nanoflakes with heights that are between this diffusion length and the optical absorption depth of ≈2 µm, which balances the competing requirements of charge transport and light absorption. Moreover, the unique stepped morphology of these CSS‐grown nanoflakes improves photocurrent by exposing multiple edge sites in every nanoflake. The optimized vertical SnS2 nanoflake photoanodes produce record photocurrents of 4.5 mA cm −2 for oxidation of a sulfite hole scavenger and 2.6 mA cm −2 for water oxidation without any hole scavenger, both at 1.23 VRHE in neutral electrolyte under simulated AM1.5G sunlight, and stable photocurrents for iodide oxidation in acidic electrolyte. Abstract : Vertically aligned SnS2 nanoflake photoanodes synthesized by a scalable close space sublimation exhibit high photoexcited carrier lifetimes (1.3 ns), intrinsic mobility (330 cm 2 V −1 s −1 ), and long diffusion length (1 µm). The highest photocurrents of 4.5 and 2.6 mA cm −2 obtained at 1.23 VRHE for sulfite oxidation and water oxidation, respectively, are attributed to the optimum nanoflake height and the unique stepped morphology.